The sweet side of the cell cycle - Tan, Ee Phie (Biochem Soc Trans, 2017)
Cell division (mitosis) and gamete production (meiosis) are fundamental requirements for normal organismal development. The mammalian cell cycle is tightly regulated by different checkpoints ensuring complete and precise chromosomal segregation and duplication. In recent years, researchers have become increasingly interested in understanding how O-GlcNAc regulates the cell cycle. The O-GlcNAc post-translation modification is an O-glycosidic bond of a single β-N-acetylglucosamine sugar to serine/threonine residues of intracellular proteins. This modification is sensitive toward changes in nutrient levels in the cellular environment making O-GlcNAc a nutrient sensor capable of influencing cell growth and proliferation. Numerous studies have established that O-GlcNAcylation is essential in regulating mitosis and meiosis, while loss of O-GlcNAcylation is lethal in growing cells. Moreover, aberrant O-GlcNAcylation is linked with cancer and chromosomal segregation errors. In this review, we will discuss how O-GlcNAc controls different aspects of the cell cycle with a particular emphasis on mitosis and meiosis.